Any day, split halfway: Flexibility in scheduling high‐dose cisplatin—A large retrospective review from a high‐volume cancer center. Issue 1 (27th February 2021) - Kang, Jung Julie; Tchekmedyian, Vatche; Mohammed, Nader; Rybkin, Alisa; Kitpanit, Sarin; Fan, Ming; Wang, Huili; Lobaugh, Stephanie M.; Zhang, Zhigang; Lee, Anna; Chen, Linda; Yu, Yao; et al.
Abstract: High‐dose (HD) cisplatin remains the standard of care with chemoradiation for locally advanced oropharyngeal cancer (OPC). Cooperative group trials mandate bolus‐HD (100 mg/m 2  × 1 day, every 3 weeks) cisplatin administration at the beginning of the week to optimize radiosensitization—a requirement which may be unnecessary. This analysis evaluates the impact of chemotherapy administration day of week (DOW) on outcomes. We also report our institutional experience with an alternate dosing schedule, split‐HD (50 mg/m 2  × 2 days, every 3 weeks). We retrospectively reviewed 435 definitive chemoradiation OPC patients from 10 December 2001 to 23 December 2014. Those receiving non‐HD cisplatin regimens or induction chemotherapy were excluded. Data collected included DOW, dosing schedule (bolus‐HD vs split‐HD), smoking, total cumulative dose (TCD), stage, Karnofsky Performance Status, human papillomavirus status and creatinine (baseline, peak and posttreatment baseline). Local failure (LF), regional failure (RF), locoregional failure (LRF), distant metastasis (DM), any failure (AF, either LRF or DM) and overall survival (OS) were calculated from radiation therapy start. Median follow‐up was 8.0 years (1.8 months‐17.0 years). DOW, dosing schedule and TCD were not associated with any outcomes in univariable or multivariable regression models. There was no statistically significant difference in creatinine or association with TCD in split‐HD vs bolus‐HD. There was no statistically significant association between DOW and outcomes, suggesting that cisplatin could be administered any day. Split‐HD had no observed differences in outcomes, renal toxicity or TCD compared to bolus‐HD cisplatin. Our data suggest that there is some flexibility of when and how to give HD cisplatin compared to clinical trial mandates. Abstract : What's new? Head and neck cancer trials mandate bolus high‐dose cisplatin administration early in the week to optimize radiosensitization—a requirement which warrants further evaluation. This large retrospective analysis found no association between the day‐of‐week of cisplatin administration and local, regional, or any failure, distant metastasis, or overall survival. Furthermore, splitting the administration of high‐dose cisplatin over two days yielded no significant difference in outcomes, renal toxicity, or cumulative dose. Altogether, the data suggest some flexibility in the administration of high‐dose cisplatin during chemoradiation therapy, potentially maximizing the convenience, compliance, and tolerability of the gold‐standard chemotherapy in locally advanced oropharyngeal cancer.